Treatment of spinal cord injury: A review of engineering using neural and mesenchymal stem cells. Issue 1 (23rd August 2014) - Mortazavi, Martin M.; Harmon, Olivia A.; Adeeb, Nimer; Deep, Aman; Tubbs, R. Shane
<x xml:space="preserve">Abstract</x> Over time, various treatment modalities for spinal cord injury have been trialed, including pharmacological and nonpharmacological methods. Among these, replacement of the injured neural and paraneural tissues via cellular transplantation of neural and mesenchymal stem cells has been the most attractive. Extensive experimental studies have been done to identify the safety and effectiveness of this transplantation in animal and human models. Herein, we review the literature for studies conducted, with a focus on the human‐related studies, recruitment, isolation, and transplantation, of these multipotent stem cells, and associated outcomes. Clin. Anat. 28:37–44, 2015. © 2014 Wiley Periodicals, Inc.